2020
DOI: 10.1111/acer.14513
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Apathy in Korsakoff Syndrome Patients Receiving Long‐Term Care With and Without Cerebrovascular Comorbidity

Abstract: Background Korsakoff syndrome (KS) is a severe neuropsychiatric disorder caused by acute deficiency of vitamin B1 and concomitant alcoholism. Patients with KS are particularly vulnerable for cerebrovascular comorbidity. KS is characterized by cognitive and neuropsychiatric symptoms, one of which is apathy. Apathy is a pathological lack of goal‐directed behaviors, goal‐directed cognitions, and goal‐directed emotions. Cerebrovascular accidents are known to carry a risk for developing apathy. Apathy has a dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In addition, we aim to relate the three dimensions of apathy to everyday functioning and overall cognitive performance. Based on previous results [ 8 , 9 , 13 , 16 , 17 ], we hypothesize that all three dimensions of apathy will be present in patients with AUD, ARCI and KS. We expect behavioral apathy to be the most frequently reported dimension of apathy in all three groups and hypothesize that especially behavioral apathy is negatively related to everyday functioning and cognitive performance.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, we aim to relate the three dimensions of apathy to everyday functioning and overall cognitive performance. Based on previous results [ 8 , 9 , 13 , 16 , 17 ], we hypothesize that all three dimensions of apathy will be present in patients with AUD, ARCI and KS. We expect behavioral apathy to be the most frequently reported dimension of apathy in all three groups and hypothesize that especially behavioral apathy is negatively related to everyday functioning and cognitive performance.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, AES-I scores were found to correlate with overall cognitive dysfunction as measured with the Montreal cognitive assessment (MoCA) and everyday executive dysfunction [16]. In another recent study [17], higher rating of general apathy (assessed using the AES-I total score) were found in patients with KS with and without cerebrovascular comorbidity, as compared to healthy controls, but no significant correlation with executive functioning was found, possibly because of the small sample size. More importantly, the AES-I does not fully cover the most current definition of apathy.…”
Section: Introductionmentioning
confidence: 99%
“…Both the implementation and clinical indiciation for virtual reality techniques were straightforward, leading to a rapid increase in observed quality of life of the patients. The request for action resulted in multiple moods and actions despite the severity of apathy following Korsakoff's syndrome (Oey et al, 2021). Results were therefore remarkable and highlight the positive effects of the use of virtual reality technology in clinical long-term care practice for Korsakoff's syndrome patients.…”
Section: Implications and Conclusionmentioning
confidence: 86%
“…Dorst and colleagues investigated the multidimensional nature of apathy in KS and concluded that social functioning is impaired, and that social apathy is most severe in KS (as compared to behavioral and emotional apathy) [66]. In line with this, KS patients have been described as 'flat and emotionally detached' [1] and Oey and colleagues describe that 'emotional blunting' (described as patients still experiencing emotions but being unable to display them) occurs in KS [67]. The negative association between apathy and social participation that we found might be explained by this.…”
Section: Apathymentioning
confidence: 98%